STAT5 promotes chronic pancreatitis by enhancing GM-CSF-dependent neutrophil augmentation. Issue 2 (28th June 2021) - Lin, Yuli; Chen, Yusheng; Feng, Wenxue; Zhang, Junfeng; Hua, Rong; Yin, Bo; Yang, Xuguang
Abstract: Chronic pancreatitis (CP) is a continuing or relapsing inflammatory disease of the pancreas, characterized by fibrosis of the whole tissue. The regulatory mechanisms of the immune microenvironment in the pathogenesis of CP are still not clear. Immune cells, especially myeloid cells, play an important role in the pathogenesis of pancreatitis. Understanding the regulatory mechanisms of immune infiltration has a significant impact on CP intervention. Here, we demonstrated that transcription factor STAT5 was involved in and critical for the progression of CP. Inflammatory stress could significantly increase the expression and activation of STAT5 during CP. STAT5 deficiency or inhibition contributed to alleviating pancreatic inflammation and fibrosis in CP mice. The increased neutrophil infiltration, mediated by up-regulated GM-CSF, was responsible for the pancreatitis-promoting activity of STAT5. Our investigation highlighted the importance of STAT5 in regulating the immune microenvironment of CP. Targeting STAT5 may hold distinct promise for clinical treatment to alleviate CP. Graphical Abstract: Up-regulated expression and activation of STAT5 increases GM-CSF expression, promotes neutrophil augmentation, and eventually exacerbates chronic pancreatitis.